2017
DOI: 10.3390/ijgi6100308
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of the Spatial Characteristics of Visible and Near-Infrared Reflectance in Predicting Soil Organic Carbon Density

Abstract: Soil organic carbon stock plays a key role in the global carbon cycle and the precision agriculture. Visible and near-infrared reflectance spectroscopy (VNIRS) can directly reflect the internal physical construction and chemical substances of soil. The partial least squares regression (PLSR) is a classical and highly commonly used model in constructing soil spectral models and predicting soil properties. Nevertheless, using PLSR alone may not consider soil as characterized by strong spatial heterogeneity and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Subsequently, the SOC content was measured using potassium dichromate [52]. All these methods can be found in the studies of Guo et al [53] and Liu et al [22].…”
Section: Study Area and Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the SOC content was measured using potassium dichromate [52]. All these methods can be found in the studies of Guo et al [53] and Liu et al [22].…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…PLSR is a popular modeling technique used in chemometric and quantitative spectral analyses. It is based on a linear transition from numerous original descriptors to a new variable space based on a small number of orthogonal factors [53,59]. This method is used to create predictive models when many highly collinear predictor variables exist [60].…”
Section: Partial Least Squares Regression (Plsr) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for the other soil properties, differences in RPIQ V were less between the algorithms (Figure 3). These effects of sample size on RPIQ V can be attributed to the combined effect of spectral information in the cross‐validation and spatial autocorrelation (Guo, Chen, et al., 2017; Guo, Zhao, et al., 2017), since both increase with increasing sample size in this field‐scale study.…”
Section: Resultsmentioning
confidence: 83%
“…The important work of this group is to choose representative auxiliary variables and remove multicollinearity and random noise among them. The third group is about combining spatial characteristics and soil covariates to construct soil prediction models, including COK, GWR and other extensional models (regression kriging and geographically weighted regression kriging model), which consider spatial autocorrelation of residuals of the prediction results (Guo et al, 2017a). Various prediction models of soil properties have been constructed in different regions of interest, and most of the publications have shown that the third class of models have better predictive accuracy and can be easily interpreted (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%